2016
DOI: 10.1038/srep32928
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and mitochondrial dysfunction in adjuvant-arthritis rats treatment with resveratrol

Abstract: Resveratrol is a polyphenol derivatives which exhibits a pro-apoptotic effect in a variety of human cancers by triggering mitochondria apoptosis pathway and autophagy. However, there are scarcely reports on its apoptosis-promoting effect in abnormal proliferation fibroblast-like synoviocytes (FLSs). In this study, we investigated the underlying mechanism and apoptosis-inducing effects of resveratrol on the abnormal proliferation of FLSs in adjuvant-arthritis (AA) rats. Since using resveratrol for 12 days resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 51 publications
2
52
0
1
Order By: Relevance
“…Previous studies showed that resveratrol activates autophagic cell death in several cancer cell lines (Selvaraj, Sun, Sukumaran, & Singh, ). However, it has also been found that resveratrol inhibits reactive oxygen species and autophagy in adjuvant‐arthritis rats (Zhang et al, ). Resveratrol suppresses hydrogen peroxide‐induced autophagy and apoptosis in cardiomyocyte cells (Huang, Ting, Huang, Yang, & Lin, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that resveratrol activates autophagic cell death in several cancer cell lines (Selvaraj, Sun, Sukumaran, & Singh, ). However, it has also been found that resveratrol inhibits reactive oxygen species and autophagy in adjuvant‐arthritis rats (Zhang et al, ). Resveratrol suppresses hydrogen peroxide‐induced autophagy and apoptosis in cardiomyocyte cells (Huang, Ting, Huang, Yang, & Lin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol‐induced autophagy has been suggested to exert beneficial effects of resveratrol (Park et al, ). However, recent studies demonstrate that resveratrol‐mediated inhibition of autophagy can antagonize oxidative injuries (Huang, Ting, Huang, Yang, & Lin, ; Zhang et al, ). In addition, resveratrol protects lung cells form PM‐induced cytotoxicity (Fahmy et al, ; Salcido‐Neyoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…6 A previous study has shown that excessive ROS induces mitophagy, 7 and feedback can remove damaged mitochondria to reduce ROS accumulation. 9 It is notable that a defect in the mitochondrial respiratory chain (MRC) complex IV, and increased autophagy (mediated by LC3 and Beclin 1) are associated with the development of RA. 9 It is notable that a defect in the mitochondrial respiratory chain (MRC) complex IV, and increased autophagy (mediated by LC3 and Beclin 1) are associated with the development of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the anti-inflammatory effect, resveratrol is considered a potential agent for RA therapy, because it is an excellent scavenger of hydroxyl, superoxide, and other radicals and improves antioxidant defenses, such superoxide dismutase (SOD), catalase, thioredoxin, and GSH-Px [ 88 , 89 , 90 ]. Zhang et al (2016) showed reducing oxidative injury parameters in adjuvant arthritis rats that were treated for 12 days with resveratrol (5, 15, 45 mg/kg) led to a significant reduction in MDA content capacity, glutathione peroxidase, and the glutathione reductase ratio [ 90 ]. Wahba, Messiha, and Abo-Saif (2016) also reported that treatment with 10 mg/kg/day of resveratrol in rats with arthritis, induced by complete Freund’s adjuvant (CFA), restored serum MDA and glutathione (GSH) levels back to normal.…”
Section: Effects Of Resveratrol On Systemic Autoimmune Diseasementioning
confidence: 99%